It - King, Stephen (Hodder & Stoughton, 2017)
It is a group of children who see - and feel - what makes Derry so horribly different. In the storm drains, in the sewers, IT lurks, taking on the shape of every nightmare, each one's deepest dread. Sometimes is appears as an evil clown named Pennywise and sometimes IT reaches up, seizing, tearing, killing . . . Time passes and the children grow up, move away and forget. Until they are called back, once more to confront IT as IT stirs and coils in the sullen depths of their memories, emerging again to make their past nightmares a terrible present reality.